Synthesis, Anticonvulsant, and Antinociceptive Activity of New 3-(2-Chlorophenyl)- and 3-(3-Chlorophenyl)-2,5-dioxo-pyrrolidin-1-yl-acetamides - Małgorzata Góra; Anna Czopek; Anna Rapacz; Anna Gębska; Katarzyna Wójcik-Pszczoła; Elżbieta Pękala; Krzysztof Kamiński (Molecules, 2021)
The new series of 3-(2-chlorophenyl)- and 3-(3-chlorophenyl)-pyrrolidine-2,5-dione-acetamide derivatives as potential anticonvulsant and analgesic agents was synthesized. The compounds obtained were evaluated in the following acute models of epilepsy: maximal electroshock (MES), psychomotor (6 Hz, 32 mA), and subcutaneous pentylenetetrazole (scPTZ) seizure tests. The most active substance-3-(2-chlorophenyl)-1-{2-[4-(4-fluorophenyl)piperazin-1-yl]-2-oxoethyl}-pyrrolidine-2,5-dione (6) showed more beneficial ED50 and protective index values than the reference drug—valproic acid (68.30 mg/kg vs. 252.74 mg/kg in the MES test and 28.20 mg/kg vs. 130.64 mg/kg in the 6 Hz (32 mA) test, respectively). Since anticonvulsant drugs are often effective in neuropathic pain management, the antinociceptive activity for two the promising compounds—namely, 6 and 19—was also investigated in the formalin model of tonic pain. Additionally, for the aforementioned compounds, the affinity for the voltage-gated sodium and calcium channels, as well as GABAA and TRPV1 receptors, was determined. As a result, the most probable molecular mechanism of action for the most active compound 6 relies on interaction with neuronal voltage-sensitive sodium (site 2) and L-type calcium channels. Compounds 6 and 19 were also tested for their neurotoxic and hepatotoxic properties and showed no significant cytotoxic effect.